Meanings and Interpretations of Spirituality in Nursing and Health - Lalani, Nasreen (Religions, 2020)
Numerous spirituality models and tools have been developed in health education and research, but a gap still exists around the conceptual clarity and articulation of spirituality among nurses and healthcare providers. Nurses and healthcare providers still find it difficult to interpret and apply the concepts of spirituality in their practice settings. This paper provides a concept analysis of spirituality using the Walker and Avant method of conceptual analysis. Several databases including conceptual and empirical literature from various disciplines have been used. The defining attributes of spirituality included spirituality and religion as a separable or mutual construct, spirituality as a personal construct, wholeness and integration, meaning making and purpose, sense of connectedness and relationship, transcendence, inner source of power, energy, and strength. Major antecedents of spirituality found were faith, personal values, and belief systems, and life adversities. Consequences of spirituality included personal/spiritual growth and wellbeing, resilience, and religiousness. Spirituality is a unique and personal human experience, an individualised journey characterised by multiple experiential accounts such as meaning making, purpose, connectedness, wholeness and integration, energy, and transcendence. Spiritual experiences are often difficult to examine and measure using scientific tools and empirical language. Healthcare providers need to fully understand and apply spirituality and spiritual care aspects to provide holistic person-centred care.